2016
DOI: 10.17507/tpls.0608.22
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Listening Comprehension in English Language Teaching

Abstract: Abstract-Listening is a significant language skill to develop in second language learning. Despite its importance, language learners consider listening as the most difficult language skill to learn. Since the role of listening comprehension in language teaching has been repeatedly emphasized, many teachers do not pay enough attention to its importance in their classes. In this paper, the researchers review some important issues concerning listening comprehension to provide a basis for developing listening skil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 27 publications
1
64
0
Order By: Relevance
“…For over 20 years, researchers (Morley, 1991;Dalton, 1997;Celce Murcia et al 2001;Wei, 2006, Gilakjani, 2012 have never ceased to agree that pronunciation is an integral part of English language teaching. However, studies (Nair, Krishnasamy, & de Mello, 2006, Jayapalan & Pillai, 2011 in Malaysia revealed the neglect over pronunciation skills in the ESL classrooms.…”
Section: Teaching Pronunciation In Malaysiamentioning
confidence: 99%
See 1 more Smart Citation
“…For over 20 years, researchers (Morley, 1991;Dalton, 1997;Celce Murcia et al 2001;Wei, 2006, Gilakjani, 2012 have never ceased to agree that pronunciation is an integral part of English language teaching. However, studies (Nair, Krishnasamy, & de Mello, 2006, Jayapalan & Pillai, 2011 in Malaysia revealed the neglect over pronunciation skills in the ESL classrooms.…”
Section: Teaching Pronunciation In Malaysiamentioning
confidence: 99%
“…This is reflected in the study by Gilakjani (2012) which reported that ESL teachers justified their negligence towards pronunciation with their limited knowledge of techniques to teach pronunciation. In addition, Baker (2011) points out that many teachers "seemed to take an ad hoc approach to teaching pronunciation when intelligibility was compromised".…”
Section: Teaching Pronunciation In Malaysiamentioning
confidence: 99%
“…With that said, our findings suggest an extremely dark profile of Kuwaiti speakers of English across various age groups. The Kuwaiti speakers are expected to use unintelligible English, due to the significant role of pronunciation on the speakers' speech intelligibility regardless of the grammatical errors it contains (Gilakjani, 2012). Future research on the topic could follow up by selecting unified word lists, in terms of their length and familiarity, so as to control any confounding factors that may play a role in the participants' sound realization ability.…”
Section: Resultsmentioning
confidence: 99%
“…A speaker of English as a foreign language who has good pronunciation is much more likely to be understood even if s/he makes grammatical errors (Gilakjani, 2012). Pronunciation is therefore very much a "must" skill for English language learners, and yet for Arabic speakers it is the skill that seems to be acquired with greatest difficulty mainly due to the various differences between the sound systems of Arabic and English.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to [24], suitable teaching in listening comprehension can decrease listening apprehension and provide a good basis for becoming independent learners who can effectively use the listening process for learning. Finally, it can be concluded that guiding learners in the process of listening provides them with the knowledge by which they can successfully complete a listening activity and puts them in control of their learning.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%